A new model for lipid monolayer and bilayers based on thermodynamics of irreversible processes - Pinto, Oscar Alejandro (2019)
Lipid monolayers are used as experimental model systems to study the physical chemical properties of biomembranes. With this purpose, surface pressure/area per molecule isotherms provide a way to obtain information on packing and compressibility properties of the lipids. These isotherms have been interpreted considering the monolayer as a two dimensional ideal or van der Waals gas without contact with the water phase. These modelistic approaches do not fit the experimental results. Based on Thermodynamics of Irreversible Processes (TIP), the expansion/compression process is interpreted in terms of coupled phenomena between area changes and water fluxes between a bidimensional solution of hydrated head groups in the monolayer and the bulk solution. The formalism obtained can reproduce satisfactorily the surface pressure/area per lipid isotherms of monolayer in different states and also can explain the area expansion and compression produced in particles enclosed by bilayers during osmotic fluxes. This novel approach gives relevance to the lipid-water interaction in restricted media near the membrane and provides a formalism to understand the thermodynamic and kinetic response of biointerphases to biological effectors.